Seawater signatures in the supracrustal Lewisian Complex, Scotland - Parnell, J.; Boyce, A.J.; Næraa, T. (Geological Magazine, 2022)
Abstract Marble in the supracrustal rocks of the Lewisian Complex, Tiree, includes chlorine-bearing amphiboles, chlorine-rich apatite, sulphur-rich scapolite, albite and phlogopite, all of which are regarded as evidence for evaporites in other metamorphosed sequences. Titanite yields U–Pb ages of ∼1.6 Ga, i.e. late Laxfordian, which excludes a younger imprint of sodium metasomatism. Traces of anhydrite, and isotopically heavy pyrite, also indicate deposition from seawater. Elsewhere in the Hebrides, tourmaline in Lewisian Complex marbles may represent seafloor exhalative deposits. Combined, the evidence suggests Lewisian Complex supracrustal marbles formed in an evaporative environment, like other Palaeoproterozoic successions across the North Atlantic region.